Adaptive elastic metastructures from magneto-active elastomers - Pierce, Connor D; Willey, Carson L; Chen, Vincent W; Hardin, James O; Berrigan, J Daniel; Juhl, Abigail T; Matlack, Kathryn H (Smart materials and structures, 2020)
Elastic metastructures provide advanced control of elastic wave propagation, particularly through their ability to exhibit frequency band gaps where elastic waves cannot propagate. Several metastructure design strategies to realize band gaps in frequency ranges of interest have emerged in recent years. However, the band gap frequencies are fixed at design time by the metastructure geometry and constituent materials. Here, a tunable metamaterial is developed which utilizes the coupled magneto-mechanical response of magnetoactive elastomers (MAE) to enable active control of the band gap frequencies. It is shown that the band gap of a lattice-based metastructure design can be tuned over a continuous frequency range by remote application of a magnetic field. A direct-ink write fabrication method is introduced to fabricate the metastructures from MAEs, which allows this concept to be extended to a vast design space. Our results suggest that the band gap tunability depends not only on the strength of the applied magnetic field, but also on the interaction of the magnetic field and the metastructure geometry. This implies that the combined effects of geometry and magnetic stiffening represent a new design parameter for tunable metastructures, enabling the creation of new smart structures which feature tunable inherent vibration control.